The possible function of Flp1 in homologous recombination repair in Saccharomyces cerevisiae - Phung, Huong Thi Thu; Nguyen, Hoa Luong Hieu; Nguyen, Dung Hoang (AIMS Genetics, 2018)
Saccharomyces cerevisiae Mus81 is a structure-selective endonuclease which constitutes an alternative pathway in parallel with the helicase-topoisomerase Sgs1-Top3-Rmi1 complex to resolve a number of DNA intermediates during DNA replication, repair, and homologous recombination. Previously, it was showed that the N-terminal region of Mus81 was required for its in vivo function in a redundant manner with Sgs1; mus81Δ120N mutant that lacks the first 120 amino acid residues at the N-terminus exhibited synthetic lethality in combination with the loss of SGS1. In this study, the physiologically important role of the N-terminal region of Mus81 in processing toxic intermediates was further investigated. We examined the cellular defect of sgs1Δmus81Δ100N cells and observed that although viable, the cells became very sensitive to DNA damaging agents. A single-copy suppressor screening to seek for a factor(s) that could rescue the drug sensitivity of sgs1Δmus81Δ100N cells was performed and revealed that Flp1, a site-specific recombinase 1 encoded on the 2-micron plasmid was a suppressor. Moreover, Flp1 overexpression could partially suppress the drug sensitivity of mus81Δ cells at 37 °C. Our findings suggest a possible function of Flp1 in coordination with Mus81 and Sgs1 to jointly resolve the branched-DNA structures generated in cells attempting to repair DNA damages.
Keywords: Flp1; genetic screening; homologous recombination repair; Mus81; Sgs1